Market efficiency and limits to arbitrage: Evidence from the Volkswagen short squeeze - Allen, Franklin; Haas, Marlene D.; Nowak, Eric; Tengulov, Angel (Journal of Financial Economics, 2021)
On October 26, 2008, Porsche announced a largely unexpected domination plan for Volkswagen. The resulting short squeeze in Volkswagen’s stock briefly made it the most valuable listed company in the world. We argue that this was a manipulation designed to save Porsche from insolvency and the German laws against this kind of abuse were not effectively enforced. Using hand-collected data we provide the first rigorous academic study of the Porsche-VW squeeze and show that it significantly impeded market efficiency. Preventing manipulation is important because without efficient securities markets, the EU’s major project of the Capital Markets Union cannot be successful.